2022
DOI: 10.3390/app12199714
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrians’ Microscopic Walking Dynamics in Single-File Movement: The Influence of Gender

Abstract: Demographics of individuals could largely influence their behaviors and interactions with surrounding pedestrians. This study investigates the influence of pedestrians’ gender on microscopic walking dynamics of single-file movements using the trajectory data collected from a controlled experiment conducted under different density levels. Instantaneous acceleration (with a time lag that varied from 0.12 s to 0.68 s) versus relative speed between the subject pedestrian and the pedestrian in front of him/her plot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Subaih et al [17] found that the mean velocity of exclusively male pedestrians is approximately the same as exclusively female pedestrians, thus there is no gender difference in pedestrian movement behavior. On the contrary, the outcomes of Dias et al [18] revealed that, in addition to relative speed, gender has a significant influence on instantaneous acceleration and deceleration for all density levels. Such contrast implies that further details on the influence of gender need to be investigated in the future.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Subaih et al [17] found that the mean velocity of exclusively male pedestrians is approximately the same as exclusively female pedestrians, thus there is no gender difference in pedestrian movement behavior. On the contrary, the outcomes of Dias et al [18] revealed that, in addition to relative speed, gender has a significant influence on instantaneous acceleration and deceleration for all density levels. Such contrast implies that further details on the influence of gender need to be investigated in the future.…”
Section: Introductionmentioning
confidence: 84%
“…The study found that pedestrians who have a higher motivation have a stronger ability to adapt their velocities. In addition, the topic of gender influence is discussed by Subaih et al [17] and Dias et al [18]. Subaih et al [17] found that the mean velocity of exclusively male pedestrians is approximately the same as exclusively female pedestrians, thus there is no gender difference in pedestrian movement behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In studies involving pedestrians, the time lag is typically referred to as the "visual-motor delay" and is generally assumed to be around 0.40 s [29,30]. The study by Dias et al [31] found that this characteristic time delay varies from 0.12 s to 0.68 s. However, a higher average delay time was reported by Xue et al [32] for the correlation between the speeds of children pedestrian pairs, where the average delay time ranged from 0.75 to 0.84 s. For micromobility vehicles, such as the Segway, the reaction time can be incorporated depending on the situation, e.g., when following a pedestrian or a cyclist and during normal following or sudden brake situations [33]. Dias et al [33] reported that the average reaction times (±SDs) of Segway riders were 0.50 s (±0.29 s) and 0.70 s (±0.44 s) when following a cyclist and a pedestrian, respectively, during sudden brake situations.…”
Section: Relationship Between Relative Speed and Accelerationmentioning
confidence: 99%
“…When we look more closely into the specific structure, it becomes clear that there are also variations depending on the experimental setup. The type of flow, such as uni-, bi-, or multidirectional streams; human factors such as age, gender, height, and culture [3,[18][19][20][21][22][23][24][25][26], or external factors such as restricted visibility [27], different height adjustments due to smoke [28], motivation or instruction [18], temperature [29], sidewalk quality [29,30], rhythm or background music [31,32], or properties of human movement, such as step length and frequency [33][34][35][36][37][38][39], all affect the fundamental diagram. This list is only exemplary and does not claim to be complete.…”
Section: Introductionmentioning
confidence: 99%